Exceptional Agulhas leakage prolonged interglacial warmth during MIS 11c in Europe - Koutsodendris, Andreas; Pross, Jörg; Zahn, Rainer (Paleoceanography, 2014)
The transport of warm and saline surface water from the Indo‐Pacific Ocean into the South Atlantic (“Agulhas leakage”) influences the Atlantic Meridional Overturning Circulation (AMOC), which in turn exerts control on European climate. Paleoceanographic data document a remarkably strong Agulhas leakage at the end of marine isotope stage (MIS) 11c interglacial (~400 ka B.P.), which is one of the best orbital analogues for the Holocene. Here we assess the potential influence of this exceptional Agulhas leakage on North Atlantic climate based on a compilation of marine and terrestrial proxy records from the Iberian margin and continental Europe.
Gesehen am 30.01.2015